DEEPER UNDERSTANDING OF CUSTOMER NEEDS UTILIZING CUSTOMER RELATIONSHIP MANAGEMENT - Darwin Yuwono Riyanto (Journal of Applied Management and Business, 2022)
Customer relationship management (CRM) helps firms adjust goods and services to customer needs. This article attempts to analyze narratively how a company's ability to maintain customer loyalty affects its financial health. Businesses must cultivate client loyalty and retention. Customer service may distinguish a company's offerings, keep consumers delighted, and improve sales and profits. Companies with loyal, satisfied customers do well. Loyal clients are inclined to speak positively about the firm and may try to recruit new customers. Customer satisfaction helps both the organization and the consumers. Businesses provide additional incentives and prizes for recurrent purchases to maintain consumer loyalty and reliability. This article finds that CRM is one of the most significant business tools since it helps companies better understand their customers and establish effective CRM systems. A customer-driven company strategy may be a response to mass advertising. Businesses respond to each customer's needs and preferences. CRM is the practice of a company actively pursuing customer relationships. Existing customers must be kept. CRM aims to enhance profitability and sales while also increasing a company's reputation with customers. Customer and corporate advantages will be explored. Repeat consumers are more likely to get long-term relationship advantages. Customers who like an organization's goods and services spend a lot of money on them.